Governança e inovação em rede APL: estudo de caso de bolsas e calçados - Simone Tiessa de Jesus Alves (2013)
Theoretical field of strategic management (FURMAN et al., 2002; Porter, 1999) report that the nations innovation capacity depends on the strength of the economic infrastructure common innovation, environmental innovation present in industrial agglomerations and the strength of linkages between micro and macro structure. Clusters are corporate networks that are configured in spatial agglomerations of firms with a productive structure specific, providing linkages (bonds) tangible and / or intangible, weak or strong local actors (and LASTRES CASSIOLLATO, 2006 , VILLELA & PINTO, 2009). Graça (2007) points out that technological innovation arises from the situation of competition in a market, stressing also the importance of governance and its structures in generating innovation capacity of cluster. In 2008, the state of Minas Gerais published a characterization of the state cluster. Thereafter, the APL handbags and shoes in the Metropolitan Region of Belo Horizonte (BHMA) joined the states clusters group, with the contribution of policies and resources. Since cluster handbags and shoes has MRBH recent establishment of its governance structure and characteristics of product innovation in the sector, the study sought to explain the role played by the cluster network governance practices and innovation of firms and bags MRBH shoes. Data were collected through 26 interviews and 21 questionnaires along to owners of enterprises and organizations to support the sector (SEBRAE, employers unions, FIEMG). The data on the types of innovations that occurred from 2009 (first year of governance actions cluster) were analyzed by descriptive statistics using SPSS 19 software. Already the factors that influenced these innovations were treated by analysis of indicators of social networks. Questions about the innovations and the factors that influenced were treated by analysis of indicators of social networks via software UCINET 6.0. After these steps, we proceeded to the triangulation the analyzes of the three data sources (interviews, documentary research and questionnaires) in order to compose the case study of cluster. It was found that the governance structure is determined by the ability of coordination of actors and a cluster command potential of their leaders, being conditioned by the productive structure of the agglomeration and the types of networks established. The analysis of innovation in cluster has demonstrated that leadership exercised by the unions have little influence on the innovation sector. In contrast, the major firms in the industry benchmark showed high potential for innovation intermediation. In this sense, it is believed that these actors can become active leaders in the governance structure of private actors, working as articulators of governance in business class.